PEDAGOGICAL VIEWS OF SMAGUL SADVOKASOV: RECONSTRUCTION OF METHODOLOGY - Mukanova G. K., Baizhumanova Z. B. (Pedagogy, Psychology, Society, 2022)
the article examines the pedagogical views of the People's Commissar of Education Smagul Sadvokasov, 1925–1927. Based on the sources, his position on the topic of the national theater and the publication of textbooks is given. Sadvokasov defended the values – the quality of textbooks and the teacher's right to creativity.
Keywords: образование; учитель; education; teacher; учебники; Казахстан; Савдокасов С; Kazakhstan; textbooks; Sadvokasov